Block ciphers identification scheme based on the distribution character of randomness test values of ciphertext - Yang WU; Tao WANG; Meng XING; Jin-dong LI (Tongxin xuebao)
By researching deficiency of current encryption algorithms identification schemes，a block ciphers identification scheme is proposed based on the distribution character of randomness test values for ciphertext.Firstly，the numbers of randomness test values for AES，Camellia，DES，3DES，SMS4 are respectively calculated based on the frequency test，frequency test in block，run test and originally clustered by the k-means algorithm.Secondly，in order to identify the block ciphers in each clustering，the dimensions of eigenvectors to the frequency test，frequency test in block，run test are calculated on the principle of reducing the comparability between eigenvectors.Eventually，the experimental results of AES，Camellia，DES，3DES，SMS4 demonstrate that the proposed scheme effectively identified the above representative block ciphers，and the correlative research can promote the further encryption algorithms identification research.